2013
DOI: 10.1002/jbm.a.34957
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid hyaluronic acid hydrogel/poly(ɛ‐caprolactone) scaffold provides mechanically favorable platform for cartilage tissue engineering studies

Abstract: Hybrid scaffolds for cartilage tissue engineering provide the potential for high stiffness properties in tension and compression while exhibiting the viscoelastic response found in hydrogels and native cartilage tissue. We investigate the impact of a hybrid scaffold fabricated from a hyaluronic acid (HA)-based hydrogel combined with porous poly(ε-caprolactone) (PCL) material formed by a particulate leaching method to study dedifferentiated chondrocyte response. The material properties of the hybrid scaffold sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…As expected, the storage modulus of the composite is greater than the hydrogel, and reduced when compared to the PCL porous scaffold alone. However, the composite does not show major changes in Young's modulus over the 6 week testing period from plain PCL scaffolds . The results from this study suggest that the hybrid scaffolds provide the potential for high stiffness properties in tension and compression, (presumably from the PCL component), while exhibiting the viscoelastic response found in hydrogels (HA) and native cartilage tissue.…”
Section: Types Of Biohybrid Materialsmentioning
confidence: 75%
See 1 more Smart Citation
“…As expected, the storage modulus of the composite is greater than the hydrogel, and reduced when compared to the PCL porous scaffold alone. However, the composite does not show major changes in Young's modulus over the 6 week testing period from plain PCL scaffolds . The results from this study suggest that the hybrid scaffolds provide the potential for high stiffness properties in tension and compression, (presumably from the PCL component), while exhibiting the viscoelastic response found in hydrogels (HA) and native cartilage tissue.…”
Section: Types Of Biohybrid Materialsmentioning
confidence: 75%
“…As seen in a comparison between PLCL/Poloxamer nanofibers with dextran/gelatin hydrogel and plain dextran/gelatin hydrogel, there was no significant difference when the polymer was incorporated, indicating that the bilayer scaffold has no detriment on cell viability . Fortunately, several studies show improved cell viability, cell adhesion and proliferation, compared to polymer alternatives or control collagen sponges . The porous nature of some composites, supported by an overall porous, or funnel like structure of the polymer base, is suggested to aid in the improved adhesion and proliferation …”
Section: Types Of Biohybrid Materialsmentioning
confidence: 99%
“…A hybrid scaffold combining HA hydrogel with porous poly(e-caprolactone) showed mechanical properties similar to that of human articular cartilage and the ability to maintain the viability, proliferation and phenotype of Canine MSCs for cartilage repair 5 a Control: treated with PBS; ASC: treated with adipose tissue-derived mesenchymal stem cells; ASC/HA: treated with ASCs + hyaluronic acid. seeded chondrocytes (Mintz and Cooper, 2014). The proliferation, chondrogenic differentiation and therapeutic potential of mesenchymal stem/stromal cells derived from the bone marrow (de Vries-van Melle et al, 2014) or adipose tissue (Wang et al, 2018) of different species were increased by culture in HA-pNIPAM (poly(N-isopropyl acrylamide) side-chains), HA/Fibrin and HA-PNIPAAm-CL (poly(N-isopropylacrylamide)) (de Vries-van Melle et al, 2014;Wang et al, 2018;Wu et al, 2018), but not in alginate/HA (de Vries-van Melle et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the combination of soft cell-laden collagen hydrogel with rigid PCL-β-TCP scaffold significantly enhanced cell retention compared to scaffolds alone ( Figure 4) and improved hydrogel-based structural and mechanical integrity compared to collagen alone (Figures 1(E) A few studies have reported the HUVEC behaviors in hybrid constructs. [15][16][17][18][19][20][21]42 . For example, Santos et al 21 (Table I) that, in turn, determined their physical properties such as porosity and surface area (Table II) and influenced their mechanical properties (Figure 1(E)).…”
Section: Discussionmentioning
confidence: 99%
“…In such hybrid constructs, in addition to support mechanically, the scaffold component provides micro-architectural guidance for cells to reorganize and form vascular networks in hydrogel within porous scaffold. A few studies have reported the in vitro cellular network formation in such hybrid constructs [15][16][17][18][19][20][21] , however, the biomechanical effects of both soft and rigid components of hybrid construct on the cellular behavior and reorganization of cells for network formation are poorly understood.…”
Section: Introductionmentioning
confidence: 99%